Investor-state arbitration and SA's bilateral investment treaty policy framework review - Klaaren, J.; Schneiderman, D. (My University, 2009)
Contribution to the DTI's review of South Africa’s bilateral investment treaty (BIT) policy framework.
Mandela Institute Working paper.
Keywords: Dispute resolution; SA's bilateral investment treaty policy; Foreign direct investment; Human rights; Sustainable development